Pérez-Amezcua, Luis Alberto. Hermes en la encrucijada. Análisis mitocrítico de las novelas líricas de los Contemporáneos. Guadalajara (México): STAUdeG, 2019, 214 pp. ISBN: 9786079427740 - Moreno Rodríguez, Ramón (Amaltea. Revista de Mitocrítica, 2020)
Bibliographic review of the book Hermes at the crossroads of Dr. Luis Alberto Pérez Amezcua. This review has an approximate length of two thousand words and promptly follows the guidelines that you establish in your prestigious magazine.